2021
DOI: 10.1111/nmo.14146
|View full text |Cite
|
Sign up to set email alerts
|

Non‐uniform gastric wall kinematics revealed by 4D Cine magnetic resonance imaging in humans

Abstract: Background Assessment of gastric function in humans has relied on modalities with varying degrees of invasiveness, which are usually limited to the evaluation of single aspects of gastric function, thus requiring patients to undergo a number of often invasive tests for a full clinical understanding. Therefore, the development of a non‐invasive tool able to concurrently assess multiple aspects of gastric function is highly desirable for both research and clinical assessments of gastrointestinal (GI) function. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…29 In a recent paper (submitted for publication around the same time as this paper), Sclocco and colleagues introduced a semi-automated processing protocol to quantify gastric emptying and motility indices from 4D cine MRI of the stomach. 30 In their study, the first MRI volume in each session was manually segmented; subsequent volumes…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…29 In a recent paper (submitted for publication around the same time as this paper), Sclocco and colleagues introduced a semi-automated processing protocol to quantify gastric emptying and motility indices from 4D cine MRI of the stomach. 30 In their study, the first MRI volume in each session was manually segmented; subsequent volumes…”
Section: Discussionmentioning
confidence: 99%
“…31 A bright intra-gastric intensity is essential to facilitate automated image segmentation. While the most common contrast meal used in gastric MRI studies is a soupbased diet or caloric liquid nutrient (eg, Ensure) with the addition of paramagnetic MRI contrast agents (eg, gadolinium chelates), 32 some studies have proposed to use naturalistic contrast meal such as blueberry or pineapple juice because they contain a high level of manganese 30,33,34 ; the use of naturalistic contrast meal is advantageous because it avoids potential safety concerns of an otherwise fabricated contrast agent. Here, we identified that firm tofu is also a high manganese food that contains 1.2 mg of manganese per 100 g tofu.…”
Section: Naturalistic Contrast Meal For Gastric Mrimentioning
confidence: 99%
See 2 more Smart Citations
“…However, no study to date has directly linked mechanoreceptive gastric afference, approximated by MRI metrics of gastric kinematics, to brainstem viscerosensory connectivity in patients with FD. In this study, we combined our previously validated 4D cine MRI gastric imaging technique 17 with brain fMRI in order to examine stomach function and the central processing of gastric afference in FD.…”
Section: Introductionmentioning
confidence: 99%